Glaucoma diagnostics using machine learning methods - Dubrovin, V. I.; Petunin, O. V. (ХНУРЕ, 2024)
The research focuses on eusage of machinel earning algorithms in glaucoma diagnostics. The objective is to analyze and compare various machine learning algorithms by constructing classification systems that verify glaucoma in ICT photos. The study involves extracting feature from photos, classifiying them using this features and evaluating the effectivenes of methods. This approach provides insights into creation of automated glaucoma diagnostic system, contributing to faster and safer medical process. Дослідження зосереджено на використанні алгоритмів машинного заробітку в діагностиці глаукоми. Мета полягає в тому, щоб проаналізувати та порівняти різні алгоритми машинного навчання шляхом побудови систем класифікації, які перевіряють глаукому на фотографіях ІКТ. Дослідження передбачає виділення ознак із фотографій, їх класифікацію за цими ознаками та оцінку ефективності методів. Такий підхід дає можливість зрозуміти створення автоматизованої системи діагностики глаукоми, що сприяє більш швидкому та безпечному процесу лікування.
Keywords: glaucoma; diagnosis; nearest neighbors method; Naive Bayes; features; machine learning; evaluation metrics; classification; sampling; глаукома; діагноз; метод найближчих сусідів; метрики оцінювання; вибірка